Case report: BRAF-inhibitor therapy in BRAF-mutated primary CNS tumours including one case of BRAF-mutated Rosai-Dorfman disease - Cronin, Christopher; McLaughlin, Ronan; Lane, Louise; Brett, Francesca M.; Jansen, Michael; Bermingham, Niamh; Wyse, Gerald; Grogan, Liam; Morris, Patrick G.; O’Reilly, Seamus (Frontiers in Medicine, 2022)
BRAF V600E oncogene mutations have been reported in multiple central nervous system (CNS) tumor types, and emerging evidence supports the use of targeted therapy in BRAF-mutated gliomas. BRAF oncogene mutations have been recently identified in Rosai-Dorfman disease (RDD)—a rare non-Langerhans cell histiocytosis. This series describes three patients from two neurosurgical centers in Ireland with BRAF V600E-mutated CNS tumors. The study participants include a 19-year-old male patient with ganglioglioma with anaplastic features, a 21-year-old male patient with CNS involvement of RDD, and a 28-year-old female patient with ganglioglioma with anaplastic features. Two patients received radiation with concurrent temozolomide before BRAF-targeted therapy. This case series describes clinical and radiological responses to BRAF-targeted therapy in BRAF V600E-mutated gliomas across multiple tumor grades and is only the second published report of response to targeted therapy in BRAF-mutated RDD. The durability of disease control with BRAF-targeted therapy was generally superior to that achieved with chemoradiation; one patient has experienced ongoing disease control for 5 years. The reported case of treatment response in BRAF-mutated RDD supports the strategy of genotyping and utilization of targeted therapy in this rare disease. The optimal sequencing of BRAF-targeted therapy in BRAF-mutated gliomas/glioneuronal tumors remains unclear, and further prospective studies are required to guide the use of genome-matched therapy in this patient population.